Pengembangan media pembelajaran video animasi menggunakan plotagon studio pada materi peluang - Hilman Mubarok; Wahyu Setiawan (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this research is to develop an animated learning video using Plotagon Studio that is feasible and practical for teaching mathematics in class. The research method used is Research and Development (R&D) with a 4D model, consisting of define, design, develop, and disseminate stages. The research was conducted at Margaasih 1 Public Middle School, involving 10 class IX students in a small-scale trial and 36 class IX students in a large-scale trial. Validation was carried out by media experts, material experts, and math teachers. Data was collected through a student response questionnaire and processed using Microsoft Excel to calculate the average. Products developed according to the 4D research method and meet the success criteria in small-scale trials with a validation percentage of media experts 60%, material experts 63%, and teachers 63%, as well as in large-scale trials with a validation percentage of media experts 85%, experts material 92%, and teachers 96%. Products that have been validated are then tested on students in small-scale trials with a percentage of 71% showing practical criteria, and large-scale trials with 86% percentage showing very practical criteria.